Temporal pole abnormalities detected by 3 T MRI in temporal lobe epilepsy due to hippocampal sclerosis: No influence on seizure outcome after surgery. (May 2017) - Casciato, Sara; Picardi, Angelo; D'Aniello, Alfredo; De Risi, Marco; Grillea, Giovanni; Quarato, Pier Paolo; Mascia, Addolorata; Grammaldo, Liliana G.; Meldolesi, Giulio Nicolo'; Morace, Roberta; Esposito, Vincenzo; Di Gennaro, Giancarlo
Highlights: Temporopolar abnormalities are common 3T MRI findings in temporal lobe epilepsy (TLE) due to hippocampal sclerosis (HS). The presence of temporopolar abnormalities could help to lateralize the epileptogenic zone in TLE-HS. The presence of temporopolar abnormalities do not influence seizure outcome in patients who had TL resection for HS. Abstract: Purpose: To assess the clinical significance of temporal pole abnormalities (temporopolar blurring, TB, and temporopolar atrophy, TA) detected by using 3 Tesla MRI in the preoperative workup in patients with temporal lobe epilepsy due to hippocampal sclerosis (TLE-HS) who underwent surgery. Methods: We studied 78 consecutive patients with TLE-HS who underwent surgery and were followed up for at least 2 years. Based on findings of pre-surgical 3 Tesla MRI, patients were subdivided in subgroups according to the presence of TB or TA. Subgroups were compared on demographic, clinical, neuropsychological data and seizure outcome. Results: TB was found in 39 (50%) patients, while TA was found in 32 (41%) patients, always ipsilateral to HS, with a considerable degree of overlap (69%) between TB and TA (p = 0.01). Patients with temporopolar abnormalities did not significantly differ from those without TB or TA with regard to sex, age, age of epilepsy onset, duration of epilepsy, history of febrile convulsions or birth complications, side of surgery, seizure frequency at surgery, presence of GTCSs, and, in particular, seizure outcome. On the other hand, TB patients show a less frequent family history of epilepsy (p < .05) while age at epilepsy onset showed a trend to be lower in the TB group (p = .09). Patients with temporopolar atrophy did not significantly differ from those without TA on any variable, except for age at epilepsy onset, which was significantly lower for the TA group (p < .05). History of birth complications and longer duration of epilepsy also showed a trend to be associated with TA (p = .08). Multivariate analysis corroborated the association between temporopolar abnormalities and absence of family history of epilepsy and history of birth complications. Conclusions: High-field 3 T MRI in the preoperative workup for epilepsy surgery confirms that temporopolar abnormalities are frequent findings in TLE-HS patients and may be helpful to lateralize the epileptogenic zone. Their presence did not influence seizure outcome.